2017
DOI: 10.1017/rdc.2017.57
|View full text |Cite
|
Sign up to set email alerts
|

Dating of Iron Age Agriculture in the Negev Highlands: A Response to Shahack-Gross and Finkelstein

Abstract: ABSTRACT. In this response to the reply by Shahack-Gross and Finkelstein (2017), we present additional data of our research at Horvat Haluqim. This includes phytolith percentages and multicellular phytolith stomata in a thin section of a layer in Terraced Field 12, dated by radiocarbon ( 14 C) to the Late Bronze-Early Iron Age. We also show thin-section evidence of aggrading sediment laminations in this terraced field. A new 14 C date is given of the Early Islamic Period in Terraced Field 7, as differences in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Bruins and van der Plicht support the former, arguing that sediment accumulation behind terraces captures datable materials that define terrace use-life. This might have been acceptable had the authors showed that they date a laminated rather than homogenous fill [which they fail to show even via micromorphology (Bruins and van der Plicht 2017a; but see Bruins and van der Plicht 2017b and our addendum below)]. Therefore, the seeming development in age along the dated profile of sediments presented by Bruins and van der Plicht (2017a: Table 1), cannot be evaluated from a sedimentological point of view.…”
Section: Introductionmentioning
confidence: 95%
See 4 more Smart Citations
“…Bruins and van der Plicht support the former, arguing that sediment accumulation behind terraces captures datable materials that define terrace use-life. This might have been acceptable had the authors showed that they date a laminated rather than homogenous fill [which they fail to show even via micromorphology (Bruins and van der Plicht 2017a; but see Bruins and van der Plicht 2017b and our addendum below)]. Therefore, the seeming development in age along the dated profile of sediments presented by Bruins and van der Plicht (2017a: Table 1), cannot be evaluated from a sedimentological point of view.…”
Section: Introductionmentioning
confidence: 95%
“…In their response to this letter, Bruins and van der Plicht (2017b) address some of the concerns raised above. We thank them for presenting additional data and for the stimulating discussion.…”
Section: Addendummentioning
confidence: 99%
See 3 more Smart Citations